MULTIFRACTAL ANALYSIS OF THE MORPHOLOGY OF THE RETINAL ARTERIES AT DIFFERENT DEGREES OF GLAUCOMATOUS DAMAGE - Ristić, Konstantin (Medicinski podmladak, 2025)
AbstractIntroduction: Glaucoma is the second leading cause of blindness worldwide. Due to its asymptomatic progression and irreversible consequences, early diagnosis is crucial. Beyond elevated intraocular pressure, retinal vascularization and morphological changes in arterial blood vessels play a significant role in the disease's pathophysiology.Aim: To determine the potential of multifractal analysis of binary images of retinal arterial blood vessels in differentiating patients with varying degrees of glaucomatous damage.Material and Methods: The study included 90 binarized images of retinal arterial blood vessels from patients with primary open-angle glaucoma, divided into three groups based on the severity of visual field damage: mild (MD < -6 dB), moderate (MD between -6 and -12 dB), and severe (MD > -12 dB). Multifractal analysis was performed using ImageJ software with the FracLac plugin. Generalized dimensions (DQ) were calculated for Q values ranging from -10 to 10. Statistical differences were analyzed using the non-parametric Kruskal-Wallis test.Results: Multifractal spectra exhibited a sigmoidal shape, confirming their multifractal nature. Significant differences between groups were observed in the central part of the spectrum (Q = 0, 1, and 2), with the severe-damage group being most distinct from the lower-damage groups. However, differences between the mild and moderate groups were not statistically significant.Conclusion: Multifractal analysis can distinguish the severe glaucomatous damage group from the lower-damage groups. The method's limited sensitivity in early stages and the relatively small sample size highlight the need for further research, including expanded analysis of additional spectra, such as Hölder exponents and singularity spectra.Keywords: multifractal analysis, retinal arteries, glaucoma, binary images
Keywords: multifractal analysis; retinal arteries; glaucoma; binary images